Design of gate valve using SolidWorks and analyses of fluid flow of the gate valve using SolidWorks Flow Simulation software - Wan Suhaimi, Wan Hanif Hazwan (2014)
This paper presents the design of gate valve using SolidWorks and the analysis of the gate fluid flow using SolidWorks Flow Simulation software. The scope of this project focus on two parts, firstly design of gate valve and secondly on analyze the fluid flow of the gate valve being designed. The gate valve was designed in detail with two and three dimensional model that consists of parts, assembly and drawings. The SolidWorks Flow Simulation was used to test the effectiveness and limitation of the gate valve that has been designed. The gate valve also has been analyzed by using fluid to observe the reaction of the gate valve. This gate valve has the ability to cut through liquids, very durable, and it is mostly used in the petroleum industry.